2010
DOI: 10.3892/or_00001014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genotype and breast cancer predisposition

Abstract: Abstract. Breast cancer is the most commonly diagnosed cancer in women. Despite recent advances in breast cancer research, a comprehensive set of genetic markers of increased breast cancer risk remain elusive. Recently mitochondrial DNA (mtDNA) mutations have been found in many types of cancer, including breast cancer. To investigate the possible role of mitochondrial genetics in breast cancer predisposition and biology we analyzed the D-loop sequence of cancer patients and assigned mitochondrial haplogroup us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 76 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Tommasi S et al, reported that the H haplogroup was associated with breast cancer tumor grade differentiation and with BRCA2 mutations [ 23 ], suggesting that mtDNA variants may act as a genetic modifier for breast cancer. While the mtDNA U haplogroup has been overrepresented in control subjects [ 24 ], the mtDNA I haplogroup has higher association with the breast cancer group [ 25 ], although there is still some controversy of the association between European mtDNA haplogroups and breast cancer risk [ 26 ]. Multiple studies have speculated that in Asian, African-American, and European-American populations, there may be an increased association between the m.10398G > A polymorphism and breast cancer [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tommasi S et al, reported that the H haplogroup was associated with breast cancer tumor grade differentiation and with BRCA2 mutations [ 23 ], suggesting that mtDNA variants may act as a genetic modifier for breast cancer. While the mtDNA U haplogroup has been overrepresented in control subjects [ 24 ], the mtDNA I haplogroup has higher association with the breast cancer group [ 25 ], although there is still some controversy of the association between European mtDNA haplogroups and breast cancer risk [ 26 ]. Multiple studies have speculated that in Asian, African-American, and European-American populations, there may be an increased association between the m.10398G > A polymorphism and breast cancer [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%